A mutual gains perspective on workplace partnership: Employee outcomes and the mediating role of the employment relations climate. (27th May 2016) - Valizade, Danat; Ogbonnaya, Chidiebere; Tregaskis, Olga; Forde, Chris
Abstract : Recent years have witnessed increased research on the role of workplace partnership in promoting positive employment relations. However, there has been little quantitative analysis of the partnership experiences of employees. This article examines how the kinds of attributions employees make regarding indirect (union‐based) and direct (non‐union‐based) employee participation in workplace partnership might influence the process of mutual gains. It uses employee outcomes to reflect partnership gains for all stakeholders involved ( i.e. employees, employers and trade unions). The article contributes to existing knowledge of workplace partnership by examining the potential role of the employment relations climate as an enabling mechanism for the process of mutual gains. The findings suggest mutual gains for all stakeholders are varied and mediated through the employment relations climate.